Managing public transport service operation in reducing travel fear factor / Rohana Sham, Mashita Sham, Khairunnisa Rahman, and Nurazlina Samsudin - Sham, Rohana; Sham, Mashita; Rahman, Khairunnisa; Samsudin, Nurazlina (2012)
The need of a woman for a safe public transport is critical especially when urban area is concerned. To be able to travel safely from point of origin to the point of destination has become a top priority for many urban woman dwellers. However, due to little research being conducted in this matter, this research attempts to fill the gap. Data were collected through bus passenger survey in three major urban areas in Penang Island. The passengers were asked to rate their safety level given the following bus service characteristics namely punctuality, comfortability, security, information and infrastructure design that are currently provided in their areas. Results from the analysis show that most women feel insecure or feel unsafe waiting too long at the bus stop if the bus is not punctual, when they are not comfortable with the level of services being provided, when there is no indication of any security measures along the journey by bus and when they receive no information of the bus services.